2007
DOI: 10.1242/jeb.02733
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mandibular loading and bite force in mammals during mastication

Abstract: SUMMARY Modulation of force during mammalian mastication provides insight into force modulation in rhythmic, cyclic behaviors. This study uses in vivo bone strain data from the mandibular corpus to test two hypotheses regarding bite force modulation during rhythmic mastication in mammals: (1)that bite force is modulated by varying the duration of force production, or(2) that bite force is modulated by varying the rate at which force is produced. The data sample consists of rosette strain data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 77 publications
4
78
1
Order By: Relevance
“…humans, 5000-22 000 s -1 (Burr et al, 1996); dog and horse, ~100 000 s -1 (Rubin and Lanyon, 1982)]. Moreover, as noted in studies of mammalian feeding (Ross et al, 2007), strain magnitude is strongly correlated with strain rate (Fig. 4), such that steps in which the femur experiences higher strains tend to be steps in which the limb is loaded more quickly.…”
Section: T Butcher and Othersmentioning
confidence: 86%
See 2 more Smart Citations
“…humans, 5000-22 000 s -1 (Burr et al, 1996); dog and horse, ~100 000 s -1 (Rubin and Lanyon, 1982)]. Moreover, as noted in studies of mammalian feeding (Ross et al, 2007), strain magnitude is strongly correlated with strain rate (Fig. 4), such that steps in which the femur experiences higher strains tend to be steps in which the limb is loaded more quickly.…”
Section: T Butcher and Othersmentioning
confidence: 86%
“…Measurements of peak strain rate from the 'dorsal' gauge location were used to determine rates of strain for mechanical property testing of the limb bones. Strain magnitudes were also regressed on strain rates from corresponding steps to evaluate the relationship between load rate and magnitude for turtle femora (Ross et al, 2007).…”
Section: In Vivo Strain Data Collection and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, highly stereotyped jaw movements may be Table3). The relationship across lepidosaurs is not significant (Ross et al, 2007b).…”
Section: Rhythmicity Efficiency and Sensorimotor Evolution In Vertebmentioning
confidence: 86%
“…The authors believed this was most likely due to an increase in the excitability of jaw closer motoneurons produced by activation of muscle spindles within the jaw closer muscles. Similarly, Ross' group recently demonstrated that bite force was modulated during SC, primarily by varying the rate at which force was generated in the jaw closers of macaques (Ross et al, 2007a). In other words, as the resistance in food properties increased, not only did the number of recruited muscle fibers increase, but the rate at which muscle fibers were recruited increased as well, so that the increased load did not significantly impact the www.intechopen.com duration of jaw closure.…”
Section: Acute Oral Rhythmicity Experimentsmentioning
confidence: 98%